Psychological Depression Factor and Productivity of Indonesia Construction Workers in Malaysia - O. Richarda, Alonge; Purbab, Ellys Juwita; Daudaa, Adebayo Adesina (School of Social Sciences, USM, 2017)
Several past research studies which are community based and some important care populations declared that depression has some consequences which are job loss, reduction of job performance and productivity, loss of life and possessions. Construction work is one out of the many job described as 3D, that's dangerous, dirty and demeaning. Malaysian construction jobs are dominated by migrant workers, which includes Indonesian migrants as well. The main aim of this study is to determine the correlates and the prevalence of depression among Indonesia migrant construction workers in Penang, Malaysia and their influence on their productivity citing construction sites in Penang state. Their level of depression was assessed using BDI (Beck depression Inventory) measurement tool. The study was conducted using a survey with semistructured questionnaire distributed to 250 numbers of Indonesian construction workers from about 20 different construction sites in Penang, Malaysia. Using SPSS description, frequency, regression and correlation analysis, the result shows that 43% of the construction workers are having mild depression, those with moderate depression are 36% and those with severe depression are 18%. This has an adverse effect on their productivity on site and their punctuality at work(Absenteeism). There is a strong statistical significance between their depression level and their productivity at work. This result will help all Site/Construction managers to be aware of construction workers’ health and ability, hence less dangerous, dirty and demeaning task. It is suggested that more research can be conducted on their resilience and ability in the near future.